2010
DOI: 10.1177/0363546510368133
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Outcomes Study of Meniscal Allograft Transplantation

Abstract: The results confirm that meniscal transplantation significantly reduces pain, decreases activity-related effusions, and improves function in patients with prior meniscectomy; however, the long-term chondroprotective effects remain unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 33 publications
1
71
0
3
Order By: Relevance
“…MMAT results in reduced patient pain, less activity-related effusions, and improved functional activities. 7,[17][18][19][20] After MMAT, LaPrade et al 7 reported a significant improvement in symptoms as measured with International Knee Documentation Committee subjective scores (preop 51.2, postop 68.2) and Cincinnati scores (preop 52.3, postop 73.2) after a minimum 2-year follow-up. Verdonk et al 18 reported a survival rate of isolated MMAT to be 72.4% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MMAT results in reduced patient pain, less activity-related effusions, and improved functional activities. 7,[17][18][19][20] After MMAT, LaPrade et al 7 reported a significant improvement in symptoms as measured with International Knee Documentation Committee subjective scores (preop 51.2, postop 68.2) and Cincinnati scores (preop 52.3, postop 73.2) after a minimum 2-year follow-up. Verdonk et al 18 reported a survival rate of isolated MMAT to be 72.4% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…An arthroscopic evaluation should be performed to determine if the patient is a suitable candidate for MMAT in cases of doubtful indication. 7,8 Uncorrected joint comorbidities are contraindications to MMAT. Concomitant procedures such as joint alignment, ligament stabilization, and cartilage resurfacing will likely improve the survival of the graft, and are encouraged to be performed in the same surgical procedure or previous to the MMAT.…”
Section: Objective Diagnosismentioning
confidence: 99%
See 3 more Smart Citations